Service marketing strategies for small and medium enterprises emerging research and opportunities - Rahman, Muhammad Sabbir 1981-; Zaman, Mahmud Habib 1981-; Hossain, Md. Afnan 1987- (IGI Global, 2019)
"This book addresses the growing importance of services and in recognition of unique challenges faced by small and medium enterprises service marketing managers to gain insights and a level playing field thereby attaining sustainability. It also focuses on the knowledge required to implement service strategies to gain competitive advantages"--
Description based on title screen (IGI Global, viewed 11/28/2018)
Keywords: Customer services / Marketing; Small business marketing; Small business / Customer services